State First? A Disaggregation and Empirical Interrogation. Issue 1 (13th January 2022) - Andersen, David; Doucette, Jonathan
Abstract: This letter is the first to systematically scrutinize the multifaceted claim that a strong state promotes democratic development. It analyzes new Varieties of Democracy data from 1789 to 2015 to specify and examine eight different versions of this 'state-first' argument in analyses that span the entire era of modern democracy. The authors document that high levels of bureaucratic quality at the time of the first democratic transition and during democratic spells are positively associated with democratic survival and deepening. By contrast, state capacity has no robust effects on democratic survival or deepening and does not condition the impact of bureaucratic quality. These findings underline the importance of particular features of a strong state as well as the importance of a disaggregated approach. They imply that democratic development is better aided by strengthening the impartiality of bureaucratic organizations than by building capacity for territorial control.